Parrett’s type models in simulated annealing algorithms - Felinskas, Gražvydas; Sakalauskas, Leonidas (Lietuvos matematikos rinkinys, 2003)
In this paper a simulated annealing algorithm for continuous global optimization is considered. There are a lot of theoretical research and very few computer modeling of efficiency of this algorithm. Modeling results, recommendations for efficiency and accuracy of the SA algorithm are given in the paper.